The psychology of social media - Mc Mahon, Ciarán (The psychology of everything, 2019)
Cover; Half Title; Series; Title; Copyright; Contents; Acknowledgements; 1 Introduction; 2 Profiles; 3 Connections; 4 Updates; 5 Media; 6 Messaging; 7 Values; Further reading; Notes
https://katalog.adlr.link/Record/0-1672205700